Impact of nanominerals on the migration and distribution of cadmium on soil aggregates. (20th July 2020) - Li, Yulong; Dong, Sufen; Qiao, Jianchen; Liang, Shuxuan; Wu, Xiaowei; Wang, Mei; Zhao, Huiwei; Liu, Wei
Abstract: Soil aggregates play an important role in the migration and transformation of heavy metals. In this paper, solution adsorption and incubation experiments were carried out to explore the effects of soil texture (sandy loam and clay loam), nanominerals (nanomontmorillonite [nMt] and nanohydroxyapatite [nHA]), and pollution levels (5, 10, and 15 mg/kg) on the surface migration and transformation of cadmium in soil aggregates with different sized particles. The aim is to clarify the dynamics of cadmium in various particle size soil aggregates of different texture soils and demonstrate the positive effect of nanominerals on the partitioning and geochemical fractions of cadmium between the aggregates. The results showed that as the particle size decreased, the ability of the soil aggregates to carry cadmium initially decreased and then increased. Organic matter was the main factor influencing the cadmium distribution among the soil aggregates, whereas soil texture had no significant effect on the adsorption capacity of Cd 2+ in the soil particles. The soil aggregates with sizes <15 μm had the highest cadmium accumulation capacity. As the cadmium concentration increased, cadmium ions were more likely to accumulate in soil aggregates with small particles (<15 μm). The application of nanominerals promoted the migration of cadmium to <15 μm particles from 2000 to 45 μm particles in sandy loam and 75-15 μm particles in clay. nHA also significantly improved the content of residual cadmium in the <15 μm portion of both soil textures. This study provides a theoretical basis for the use of nano-fixatives in environmental restoration applications. Graphical abstract: Image 1 Highlights: Chemical adsorption was the main process of cadmium on soil particles. Organic matter and Fe affected the adsorption of Cd on particles of various sizes. Cadmium prefer to accumulate in smaller aggregates. Nanohydroxyapatite promoted Cd conversion to the residual in the < 15 μm fraction.